Optimization of Restaurant Tax Revenue in Increasing Local Original Income of Gowa Regency - Muhammad Khaedar Sahib; Muhaimin Muhaimin; Andi Mifta Putri Wulansari (Jurnal Riset Perpajakan: Amnesty, 2024)
The purpose of this research is to find out the optimization of restaurant tax revenue in increasing the original income of Gowa Regency and to find out the contribution of restaurant tax in the original income of Gowa Regency. The object of this final project research is "Restaurant Tax in 2021-2023". The data used in this final project research is in the form of data sourced from the Gowa Regency Regional Revenue Agency, namely the restaurant tax target, the realization of restaurant tax and the realization of the original regional revenue. The method used in this assignment research is a qualitative method. The data collection technique used is by using interview, observation, field research and documentation studies with the data analysis technique used is applied qualitative data analysis technique.  The results of research and discussion of the optimization of restaurant tax revenue and the contribution of restaurant taxes to the original revenue of the Gowa Regency region show that the Optimization of Restaurant Tax Revenue in Gowa Regency has been optimal from 2021 to 2023. However, the percentage has fluctuated in the 3 (three) years. The contribution of Restaurant Tax to Regional Original Revenue is still in the criteria of very low with a percentage figure in 2021 to 2023 below 10%. Nevertheless, restaurant taxes still play an important role in the original revenue of Gowa Regency in supporting optimal regional development